How Covid-19 unveils the blurred borderlines between research and clinical practice monitoring: the use case of data protection and consent (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
In the EU, the race to find Covid-19 treatment solutions has been going hand in hand with the acceleration of authorisation procedures for medicines and medical devices, and regulatory actions to monitor promising off-label and compassionate uses. This arguably contributes to the ongoing blurring of the borderlines between research and clinical practice monitoring. This article aims to map the ethical and legal implications of this trend for data protection and informed consent in pre-marketing and post-marketing studies on medicines and medical devices in the context of the Covid-19 public health emergency.
Keywords: Clinical trial regulation; Covid-19; Data protection; Informed consent; Pharmaceutical and medical device regulation